Reconceptualizing Information Literacy as Social Practice Through Project-Based Service Learning in Library and Information Science - Marlini, Marlini; Barawi, Mohamad Hardyman bin; Erlianti, Gustina; Rahmah, Elva; Asmara, Rini; Desriyeni, Desriyeni (Program Studi Ilmu Perpustakaan UIN Alauddin, 2026)
Background: The rapid proliferation of digital information has intensified the need for robust information literacy (IL) competencies in higher education. Many Library and Information Science (LIS) curricula rely on decontextualized instructional designs, which often limit students' ability to apply these critical skills within authentic social frameworks. Purpose: This study evaluates the efficacy of a Project-Based Service Learning (PjBSL) model, developed using the ADDIE instructional framework, in enhancing the applied information literacy outcomes of undergraduate LIS students. Methods: The researchers employed a quasi-experimental pretest-posttest design involving 60 students. Participants were divided into experimental and control cohorts (n = 30 per group). Data were synthesized from expert validation, student practicality surveys, ACRL-aligned performance rubrics, and standardized learning assessments. Findings: The PjBSL model demonstrated exceptional validity (ICC = 0.922) and high practicality (M = 89.3). Notably, the experimental group showed significant performance gains over the control group (p < 0.001), supported by a remarkably large effect size (d = 2.61). Originality/Value: The findings indicate that integrating structured community-based projects transforms information literacy from a theoretical exercise into a socially contextualized practice. This research offers a scalable pedagogical shift for LIS education, bridging the gap between classroom instruction and real-world application.